Phase-space Rényi entropy, complexity and thermodynamic picture of density functional theory - Nagy, Á. (Journal of mathematical chemistry, 2023)
Phase-space Rényi entropy and complexity are defined within the thermodynamic picture of density functional theory. The structural entropy defined by Pipek, Varga and Nagy, the LMC statistical complexity introduced by López-Ruiz, Mancini and Calbet and generalized complexity proposed by López-Ruiz, Nagy, Romera and Sanudo are extended to the phase space. It is shown that in case of constant local temperature the logarithm of the phase-space LMC complexity reduces to the position-space structural entropy defined by Pipek et al.